Differential post‐transcriptional regulation of IL‐10 by TLR2 and TLR4‐activated macrophages. (16th December 2013) - Teixeira‐Coelho, Maria; Guedes, Joana; Ferreirinha, Pedro; Howes, Ashleigh; Pedrosa, Jorge; Rodrigues, Fernando; Lai, Wi S.; Blackshear, Perry J.; O'Garra, Anne; Castro, António G.; Saraiva, Margarida
<x xml:space="preserve">Abstract</x> The activation of TLRs by microbial molecules triggers intracellular‐signaling cascades and the expression of cytokines such as IL‐10. Il10 expression is tightly controlled to ensure effective immune responses, while preventing pathology. Maximal TLR‐induction of Il10 transcription in macrophages requires signaling through the MAPKs, ERK, and p38. Signals via p38 downstream of TLR4 activation also regulate IL‐10 at the post‐transcriptional level, but whether this mechanism operates downstream of other TLRs is not clear. We compared the regulation of IL‐10 production in TLR2 and TLR4‐stimulated BM‐derived macrophages and found different stability profiles for the Il10 mRNA. TLR2 signals promoted a rapid induction and degradation of Il10 mRNA, whereas TLR4 signals protected Il10 mRNA from rapid degradation, due to the activation of Toll/IL‐1 receptor domain‐containing adaptor inducing IFN‐β (TRIF) and enhanced p38 signaling. This differential post‐transcriptional mechanism contributes to a stronger induction of IL‐10 secretion via TLR4. Our study provides a molecular mechanism for the differential IL‐10 production by TLR2‐ or TLR4‐stimulated BMMs, showing that p38‐induced stability is not common to all TLR‐signaling pathways. This mechanism is also observed upon bacterial activation of TLR2 or TLR4 in BMMs, contributing to IL‐10 modulation in these cells in an infection setting.